Pelanggaran Hukum Perlindungan Konsumen Terhadap Penggunaan Produk Plastik berbahaya Sebagai Kemasan Makanan dan Minuman - Purwanta, Mahendra Adhi (Jurnal Hukum dan Peradilan, 2012)
Plastics contain hazards that can endanger consumers' health. This thesis discusses the problems faced by consumers due to the use of plastic products as food packaging, consumer protection law violations by the business, and the role of government in order to control the use of plastic products by businesses. Results of this study concluded that the problems faced by consumers is the use of plastic products by dangerous business as a packaged food. By using dangerous plastic product, businesses have also violated provisions of the law of consumer protection. Furthermore, the government should monitor the use of plastic packaging, provide counseling to consumers and businesses, and require businesses to include the symbol and code information on the triangle and plastic packaging. Keyword: Plastics, food packaging, consumer protection law violations